Arvari [Electronoic Resources] - Centre for Science and Environment; Centre for Science and Environment (New Delhi, India) (New Delhi Centre For Science And Environment, 2010)
Documentary about a small dry river, Arvari, which originates in Alwar, Rajasthan and now perennial through the efforts of the villagers assisted by Tarun Bharat Sangh, a local voluntary organisation. This is a success story of constructing small harvesting structures called "Johad" in a village in 1987 and in 1999, The Arvari River Parliament was organized to manage and solve water related issues.
743 Mb
Keywords: Water-storage --India --Alwar (District)